Usability of a digital tool to support long‑lasting insecticide net distribution in Northern Bahr el Ghazal State, South Sudan - Khan, Jamshed; Mubiru, Denis; Chestnutt, Elisabeth G.; Cook, Louise; Riiny, Lual L.; Okot, Francis; Chong, Kediende; Tieng, Matur T.; Zabbeh, Tombari; Okafor, Joshua; Nnaji, Chuks A. (Malaria Journal, 2024)
Long-lasting insecticidal nets (LLINs) have been a widely used malaria prevention method for decades. In South Sudan, LLINs are typically distributed by volunteers who use paper-based systems to collect distribution data. Paper-based systems are simple to use but have a higher occurrence of data inaccuracies and can hinder the timely use of data for decision-making. In 2022, a digital tool was introduced to collect data during the LLIN campaign in Northern Bahr el Ghazal (NBeG). The tool aimed to improve the accuracy of data entry and enable data to be used in real-time for decision making during the campaign. The digital tool was developed with offline functionality and interoperability with DHIS2 tracker version 2.8 in DHIS2 version 2.38. This study assessed the usability of the tool according to user perspectives. Methods A questionnaire containing open- and closed-ended questions was conducted with users of the digital tool, supervisors and other key stakeholders in five counties of NBeG. The questionnaire was administered using Malaria Consortium’s Projects Results System Android mobile application. Usability was determined through a modified and validated System Usability Scale (SUS) approach. Results A total of 93 participants responded to the usability questionnaire. The mean (± standard deviation) usability score across 10 SUS-scoring items was 60.91 (12.87), indicating a modest level of usability. The majority of users agreed the tool was useful for managing the LLIN distribution workflow, was easy to use, reduced workload, and supported stock management and real-time campaign monitoring. There was no significant difference in the usability scores across genders, roles, and counties. Respondents with experience of both paper-based and the digital tool tended to express a preference for the digital tool over paper-based systems. The majority of respondents also reported they would recommend the digital tool to colleagues. Conclusion Digital tools are perceived to improve data collection during LLIN campaigns, even in remote areas where network coverage is challenging. Additional improvements can be implemented to overcome operational challenges and improve usability of the tool. Further study is needed to assess the impact of the digital tool on data quality and real-time data use.